ANALISIS KUNJUNGAN LANSIA DALAM KEGIATAN POSYANDU DI WILAYAH KERJA PUSKESMAS PINTU LANGIT KEC. PADANGSIDIMPUAN ANGKOLA JULU KOTA PADANGSIDIMPUAN TAHUN 2019 - Betti Agustina Nasution; Namora Lumongga Lubis; Tengku Moriza (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
ABSTRACTOvercoming a variety of health problems for the elderly, the government has made various health care policies for elderly people, one of them is the posyandu for the elderly. Facts on the ground, few elderly people use the elderly posyandu and there are still many elderly people who do not visit for various reasons. The purpose of this study was to analyze qualitatively the influence of elderly visits in posyandu activities. This type of research is qualitative research. The research was conducted in the Work Area of Pintu Langit Health Center in Padangsidimpuan Sub-District, Angkola Julu, Padangsidimpuan City. Research informants were 10 people. Qualitative data analysis with stages of data reduction, data display, and conclusion or verification. The results showed that the elderly were members of the elderly posyandu in the last 2-3 years, but all were not routine or were not active. The reason is not routine because he is lazy, while working in a garden / field, does not remember the schedule of the elderly posyandu. Many elderly people do not know about the elderly posyandu related to the benefits and objectives. The attitude of ordinary elderly people has an impact on enthusiasm or interest in the posyandu is low. The distance between the house and the elderly posyandu is not too far away but there are also those who need transportation equipment to reach it. Some elderly people get support from their families (children / grandchildren) by telling the elderly posyandu schedules, delivering them to the elderly posyandu, but there are also those who do not get support. Elderly considers that the visit to the elderly posyandu is not a necessity if it is not sick. It is recommended that health workers improve the activities of the elderly program by providing counseling to increase knowledge, change negative attitudes, change perceptions about needs. Extension also to elderly families. Keywords : Elderly Visits, Elderly Posyandu